2020
DOI: 10.1111/jgh.15310
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of anti‐HBc quantification in hepatitis B virus related acute‐on‐chronic liver failure

Abstract: Background and Aim It has been reported that serum quantification of anti‐HBc (qAnti‐HBc) could predict antiviral response in chronic hepatitis B (CHB) patients, while its role in hepatitis B virus‐related acute‐on‐chronic liver failure (HBV‐ACLF) remains unclear. Its implication in HBV‐ACLF was evaluated in this study. Methods Baseline serum qAnti‐HBc levels were retrospectively detected in HBV‐ACLF and CHB patients using recently developed double‐sandwich immunoassay. The association of qAnti‐HBc level with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
0
8
0
3
Order By: Relevance
“…We previously demonstrated the role of core coding protein in immunopathogenesis (3). We also found that severe cases of HBV infection had higher HBcAb levels, while in the terminal stage, lower HBcAb level was correlated with poor outcomes (12). Based on these considerations, the immunogenicity of core-related proteins during HBV infection might be complex, yet important.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We previously demonstrated the role of core coding protein in immunopathogenesis (3). We also found that severe cases of HBV infection had higher HBcAb levels, while in the terminal stage, lower HBcAb level was correlated with poor outcomes (12). Based on these considerations, the immunogenicity of core-related proteins during HBV infection might be complex, yet important.…”
Section: Discussionmentioning
confidence: 91%
“…We previously found that overactivated HBV immunity in patients could be HBV core coding proteins related (11). We also discovered that the HBcAb level possessed a prognostic value in severe cases (12), albeit in a biphasic manner.…”
Section: Introductionmentioning
confidence: 87%
“…Since the host’s hyper-inflammatory status seems responsible for multisystem organ failure and high mortality, an immune-related marker is expected to be a good choice for clinical prognosis. The first study that investigated the performance of qAnti-HBc level in patients with ACLF demonstrated that qAnti-HBc level was significantly higher in patients with ACLF than in patients with CHB regardless of the HBeAg status [ 36 ]. On the other hand, the qAnti-HBc level was notably lower in patients with the fatal outcome than in patients who survived ACLF.…”
Section: Clinical Utility Of Qanti-hbcmentioning
confidence: 99%
“…[ 35 ] (differentiation between acute infection and acute CHB exacerbation), ref. [ 36 ] (diagnosis of acute-on-chronic liver failure), refs. [ 20 , 27 , 28 , 37 , 38 ] (diagnosis of OBI), refs.…”
Section: Figurementioning
confidence: 99%
“…This study found the HBV-ACLF patients had a significantly higher level of anti-HBc than CHB patients (4.95 ± 0.54 vs. 4.47 ± 0.84 log10 IU/mL), and the qAnti-HBc showed a comparable and complementary prognostic accuracy to MELD (model for end-stage liver disease) score in predicting clinical outcome (survival or death). A high level of qAnti-HBc was associated with less mortality in HBV-ACLF patients [ 72 ]. In another study conducted in HBV-infected patients who received orthotopic liver transplantation (OLT), Lou et al also suggested a high level of pre-transplantation qAnti-HBc was associated with a low risk of post-transplantation HBV recurrence [ 73 ].…”
Section: Prognostic and Predictive Roles Of Qanti-hbc In Chronic Hbv ...mentioning
confidence: 99%